Penguatan Kapasitas Aparatur Pemerintahan Desa Para, Kecamatan Tatoareng, Kabupaten Kepulauan Sangihe - Katerina Bataha; Donald K Monintja; Sintia M Rawis (GOTAVA, 2026)
Capacity building for village officials is essential for strengthening public services and local governance, particularly in remote island settings. This community service programme aimed to improve the capacity of stakeholders in Desa Para to prepare a participatory, evidence-informed, and sustainable Village Medium-Term Development Plan (RPJMDes). The programme involved 15 participants: 10 village officials, three members of the Tourism Awareness Group, and two members of the Village Elders Council. Activities were delivered through interactive lectures, guided practice, and group discussions. Evaluation was formative and qualitative, based on participant engagement, completion of planning exercises, group outputs, and facilitator observations. The process indicated improved understanding of sustainable village development, adaptive governance, community participation, and the strategic function of RPJMDes. Participants were also able to identify local potentials and problems, apply SWOT and needs analyses, formulate strategic objectives, and begin preparing priority-programme matrices. However, the absence of standardized pre- and post-tests means that the magnitude of change could not be quantified. Continued mentoring is required to strengthen data literacy, programme indicators, and finalization of the RPJMDes document.